Financing the security and defense sector through collective investment institutions: international experience and prospects for Ukraine - Pianov, S. V.; П'янов, С. В. (Актуальні питання розвитку сектору безпеки і оборони (зарубіжний досвід) : зб. тез доп. учасників ХХVІ Міжнар. наук.-практ. конф. інозем. мовами для здобувачів освіти (м. Вінниця, 4 квіт. 2025 р.). – Вінниця : ХНУВС, 2025. – С. 207-208, 2025)
Зазначено, що залучення інститутів спільного інвестування до фінансування сектору безпеки та оборони є перспективним напрямом. Він може сприяти розвитку військово-промислового комплексу України. Міжнародний досвід демонструє ефективність використання інвестиційних фондів, венчурного капіталу та державно-приватного партнерства у забезпеченні оборонної спроможності.

It is noted that the involvement of joint investment institutions in financing the security and defense sector is a promising direction. It can contribute to the development of the military-industrial complex of Ukraine. International experience demonstrates the effectiveness of using investment funds, venture capital and public-private partnerships in ensuring defense capabilities.
Keywords: фінансування; сектор безпеки і оборони; інститути спільного інвестування; Україна; міжнародний досвід; financing; security and defense sector; joint investment institutions; Ukraine; international experience